DEVELOPMENT AND VALIDATION OF REVERSE PHASE-HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY TECHNIQUE FOR THE CONCOMITANT ASSESSMENT OF OMEPRAZOLE AND PIPERINE IN BULK FORM - E, Susithra; Ch, Pavani (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The immense literature study was carried out and disclosed that here no method arrived for the concomitant assessment of omeprazole and piperine in bulk form by using RP-HPLC. Hence, an effort was assembled to arise a easy, specific, precise, reliable, linear, rapid, and validated reverse phase-high-performance liquid chromatography (RP-HPLC) technique for the simultaneous assessment of omeprazole and piperine in bulk form. Methods: The chromatographic analysis of omeprazole and piperine was performed using a RP-HPLC (WATERS) provided with autosampler and ultraviolet (UV) detector with the software of EMPOWER Version 2. The chosen conditions were isocratic separation with two mobile phase composed of acetonitrile:buffer (phosphate buffer: pH 6.5 ± 0.1) (55:45). Detection was carried out using UV/visible double-beam spectrophotometer at 320 nm. The method was validated as per the ICH guidelines. Results: The retention time for omeprazole and piperine by proposed HPLC method was found to be 2.767 and 4.029 min, respectively. The correlation coefficients are 0.999. The developed chromatographic method was found to be accurate with recovery 99.2–99.8% and was found within the acceptance criteria (i.e., 98.0–102.0%) with acceptable % relative standard deviation of not >2% at each level. Conclusion: Thus, the proposed HPLC procedure for the concomitant assessment of omeprazole and piperine was accurate, precise, linear, robust, simple, and economic.